Thermal Transformation of Molecular Ni2+-N-4 Sites for Enhanced CO2 Electroreduction Activity - Sa, Young Jin; Jung, Hyejin; Shin, Dongyup; Jeong, Hu Young; Ringe, Stefan; Kim, Hyungjun; Hwang, Yun Jeong; Joo, Sang Hoon (AMER CHEMICAL SOC, 2020)
Atomically dispersed nickel sites complexed on nitrogen-doped carbon (Ni-N/C) have demonstrated considerable activity for the selective electrochemical carbon dioxide reduction reaction (CO2RR) to CO. However, the high-temperature treatment typically involved during the activation of Ni-N/C catalysts makes the origin of the high activity elusive. In this work, Ni(II) phthalocyanine molecules grafted on carbon nanotube (NiPc/CNT) and heat-treated NiPc/CNT (H-NiPc/CNT) are exploited as model catalysts to investigate the impact of thermal activation on the structure of active sites and CO2RR activity. H-NiPc/CNT exhibits a similar to 4.7-fold higher turnover frequency for CO2RR to CO in comparison to NiPc/CNT. Extended X-ray absorption fine structure analysis and density functional theory (DFT) calculations reveal that the heat treatment transforms the molecular Ni2+-N-4 sites of NiPc into Ni+-N3V (V: vacancy) and Ni+-N-3 sites incorporated in the graphene lattice that concomitantly involves breakage of Ni-N bonding, shrinkage in the Ni-N-C local structure, and decrease in the oxidation state of the Ni center from +2 to +1. DFT calculations combined with microkinetic modeling suggest that the Ni-N3V site appears to be responsible for the high CO2RR activity because of its lower barrier for the formation of * COOH intermediate and optimum *CO binding energy. In situ/operando X-ray absorption spectroscopy analyses further corroborate the importance of reduced Ni+ species in boosting the CO2RR activity.
Keywords: EFFICIENT ELECTROCATALYTIC ACTIVITY; ELECTROCHEMICAL REDUCTION; CARBON-DIOXIDE; ORGANIC FRAMEWORKS; OXYGEN REDUCTION; SINGLE ATOMS; NICKEL SITES; METAL; SELECTIVITY; CATALYSTS